Renewable energy focus handbook - (Sorensen), Bent Sorensen; Breeze, Paul.; Storvick, Truman; Yang, Shang-Tian.; Rosa, Aldo V. da.; Gupta, Harsh K.; Sukanta, Roy.; Doble, Mukesh; Maegaard, Preben; Pistoia, Gianfranco; Kalogirou, Soteris ([S.l.] : Academic Press, 2009)
A one-stop desk reference, for engineers involved in renewable energies, this book will not gather dust on the shelf. It brings together the essential professional reference content from leading international contributors in the field. The full range of renewable energies are explored, including solar, wind, geothermal and bioenergy. * A hard-working desk reference, providing all the essential material needed by energy and environmental engineers on a day-to-day basis * Fundamentals, key techniques, engineering best practice and rules-of-thumb together in one quick-reference sourcebook * Definitive content by the leading authors in the field, including Bent Sorensen, Paul Breeze, Galen Suppes and Truman Storvick.